University students' solution processes in systems of linear equation - AYDIN, EMİN (ELSEVIER SCIENCE BV, 2014)
The focus of the study is system of linear equations which is one of the important topics of linear algebra. The aim is to investigate how university students' skills in the process of solving systems of linear equations by focusing on how they perform operations with matrices. This study is a case study based on a non-positivist paradigm with interpretivist approach. Findings indicate that candidates face differing levels difficulties in conceptualizing and doing operations in their solutions. (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: systems of linear equation; matrix; solution process